Towards the design for a new Bible translation in Sesotho - T. J. Makutoane; J. A. Naudé (Acta Theologica)
The purpose of this article is to suggest a means of translating the Bible and other religious texts to provide for the needs of a community consisting to a large extent of members not able to read written texts. Colonialism in Southern Africa introduced the Bible and Western text-based literacy. Bible translators have focused their efforts on preparing a clear, natural and accurate written/printed text, with the expectation that audiences will understand the message if it is in their own language. Such translations depend on the reader’s ability to understand a written text. Literacy is essentially about control of information, memory, beliefs and distribution. Users still living in an oral culture are excluded. Continuing oral traditions and indigenous forms of cultural expression were and still are beyond the control of literacy. Within these communities, the African oral story-telling tradition survived in several forms within the narrative discourse. In view of the fact that these religious communities consist predominantly of members not able to read writen texts, another vehicle for the transfer of religious thought in Bible and religious translation is suggested. A new trend in Bible translation will consider the requirements of the hearer as well as those of the reader. (The translation has to be read out aloud, heard and listened to.) This trend is reflected in the recently published Contemporary English Version (1995), Das Neue Testament (1999), The Schocken Bible, Volume 1 (1995) and the Nieuwe Bijbel Vertaling (New Dutch Version) (2004). This article’s key issue is that of a translation strategy applicable to the audiences in question. Walter J. Ong mentions nine qualities of oral culture in which he characterises orally expressed thought and expression as opposed to literate thought and expression. The implementation of the features pertaining particularly to the Sesotho oral culture is suggested for the Bible and the religious translation process in Sesotho. These features will assist hearers to grasp the meaning when the translation is read out aloud to them in church or privately.